Rabies in Iran: Past, Present and Future - Alireza Gholami; Ahmad Fayaz; Firouzeh Farahtaj (Pasteur Institute of Iran, 2014)
Introduction : Rabies is a disease that has been known since antiquity. It is a highly fatal acute disease of the central nervous system caused by a lyssavirus. Prior to the discovery of the rabies vaccine, rabies-infected individuals fell victim to the delusions and superstitions associated with this disease. Though it has been neglected in many regions of the world, rabies remains one of the most feared diseases in many developing countries, where it takes the majority of its victims. The virus circulates mainly in domestic and wild carnivores, taking 60,000 human lives worldwide every year and inflicting significant financial damage. It can, however, be well controlled due to the availability of effective Post-Exposure Prophylaxis (PEP) protocols. Pasteur Institute of Iran has had a significant role in the establishment of current PEP protocols in the world. In spite of the availability of effective PEP protocols, preventive vaccination would be preferable in endemic regions. Annually, a considerable number of exposures to animal bites occur in Iran. The current situation in the country is well-controlled by virtue of a robust surveillance system and efficient PEP treatments, resulting in considerably low death incidences from rabies. High quality vaccines recommended by the World Health Organization (WHO) are expensive and unaffordable in developing countries, where the need for rabies vaccination is greatest. Therefore, there is an increasing need to develop new cost-effective and efficient vaccines requiring fewer injections and providing longer-lasting immunity. J Med Microbiol Infec Dis, 2014, 1 (2): 10 pages.